Indoor gas pipeline leakage hidden danger monitoring system - ZHU LIYAN; JIANG WEIYANG; YU CHENXING; CHEN YALI; HU YIFEI; AO JIANFENG (2024)
The invention relates to the technical field of gas pipeline monitoring, in particular to an indoor gas pipeline leakage hidden danger monitoring system. The combustible gas detection module comprises a detection alarm, and the detection alarm is used for monitoring the concentration of combustible gas in air at the position where the combustible gas detection module is located; the intelligent linkage measurement and control valve is used for controlling the gas source supply state of the gas utilization equipment; and the cloud platform evaluates the leakage risk of the indoor pipeline based on the leakage evaluation model according to the detected air pressure and air temperature data in the home-entry gas pipeline and the gas consumption of the gas consumption equipment. The indoor leakage risk is remotely evaluated through the leakage evaluation model, and the use safety guarantee of the indoor gas pipeline system is further improved; rapid leakage risk assessment and accurate leakage risk assessment are